The chess queen enigma a Stoker & Holmes novel - Gleason, Colleen (Chronicle Books, 2015)
In 1889 London, vampire-hunter Evaline Stoker and investigator Mina Holmes once again join forces at the request of the Princess of Wales...this time their mission is to escort and protect a princess who is part of a trade mission from Betrovia, a country which has had a rocky relationship with England, starting with a four hundred-year-old dispute over a valuable Byzantine chessboard